2023
DOI: 10.1177/03611981231172956
|View full text |Cite
|
Sign up to set email alerts
|

Optimization-Based Intersection Control for Connected Automated Vehicles and Pedestrians

Abstract: Traffic at larger or busier urban intersections is currently coordinated using traffic signals to prevent dangerous traffic situations and to regulate the flow of traffic. In future scenarios with 100% connected automated vehicles, conventional traffic signals could be replaced, and vehicles at intersections could be seamlessly coordinated via vehicle-to-vehicle and vehicle-to-infrastructure communication. In the past two decades, many such control strategies have been presented, commonly referred to as autono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
2
1
Order By: Relevance
“…(ii) During the acceleration phase (phase IV), the average acceleration for AVs is around 1.09 m/s 2 , which is within the range specified in the literature (26). The maximum acceleration is about 2.02 m/s 2 , which is lower than the value assumed for AVs in Niels et al (19) (3.0 m/s 2 ), but higher than the upper acceleration for AV in S xentu¨rk Berktas x and Tanyel (12) (1.4 m/s 2 ). The starting response time to green light of HDVs is 0.70 s, which is slightly shorter than Clement et al (17) and Abraham (20), which reported values between 0.8 and 0.9 s. Contrary to the much shorter response time expected in the literature (19,13,20), it is 1.01 s for AVs which is comparable to or slightly longer than HDVs (6).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…(ii) During the acceleration phase (phase IV), the average acceleration for AVs is around 1.09 m/s 2 , which is within the range specified in the literature (26). The maximum acceleration is about 2.02 m/s 2 , which is lower than the value assumed for AVs in Niels et al (19) (3.0 m/s 2 ), but higher than the upper acceleration for AV in S xentu¨rk Berktas x and Tanyel (12) (1.4 m/s 2 ). The starting response time to green light of HDVs is 0.70 s, which is slightly shorter than Clement et al (17) and Abraham (20), which reported values between 0.8 and 0.9 s. Contrary to the much shorter response time expected in the literature (19,13,20), it is 1.01 s for AVs which is comparable to or slightly longer than HDVs (6).…”
Section: Discussionsupporting
confidence: 71%
“…The maximum acceleration is about 2.02 m/s 2 , which is lower than the value assumed for AVs in Niels et al ( 19 ) (3.0 m/s 2 ), but higher than the upper acceleration for AV in Şentürk Berktaş and Tanyel ( 12 ) (1.4 m/s 2 ). The starting response time to green light of HDVs is 0.70 s, which is slightly shorter than Clement et al ( 17 ) and Abraham ( 20 ), which reported values between 0.8 and 0.9 s. Contrary to the much shorter response time expected in the literature ( 19 , 13 , 20 ), it is 1.01 s for AVs which is comparable to or slightly longer than HDVs ( 6 ). In addition, some HDVs have a response time that is shorter than 0 s, meaning that they anticipate the green light and tend to react before the light turns green.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations